Experimental Study of Pyrite Oxidation at 100 °C: Implications for Deep Geological Radwaste Repository in Claystone - Verron, Héloïse; Sterpenich, Jérôme; Bonnet, Julien; Bourdelle, Franck; Mosser-Ruck, Régine; Lorgeoux, Catherine; Randi, Aurélien; Michau, Nicolas (Minerals, 2019)
ACL International audience The oxidation of pyrite is one of the near field processes of the chemical evolution of clay rock planned to host a deep geological radioactive waste repository during operation. Indeed, this process can lead to transitory acidic conditions in the medium (i.e., production of sulphuric acid, carbonic acid) which may influence the corrosion kinetics of the carbon steel components of some disposal cells. In order to improve the geochemical modelling of the long-term disposal, the oxidation of pyrite in contact with clays and carbonates at 100 degrees C must be evaluated. In this study, special attention was paid to the pyrite oxidation rate thanks to an original experimental set-up, involving several pyrite/mineral mixtures and a reactor coupled to a micro gas chromatograph (P-O2 and P-CO2 monitoring). Although thermodynamic modelling expects that hematite is the most stable phase in a pure pyrite heated system (low pH), experiments show the formation of native sulfur as an intermediate product of the reaction. In the presence of calcite, the pH is neutralized and drives the lower reactivity of pyrite in the absence of native sulfur. The addition of clay phases or other detrital silicates from the claystone had no impact on pyrite oxidation rate. The discrepancies between experiments and thermodynamic modelling are explained by kinetic effects. Two laws were deduced at 100 degrees C. The first concerns a pure pyrite system, with the following law: rPy= 10-4.8 center dot PO20.5 center dot t-0.5. The second concerns a pyrite/carbonates system: rPy+Ca= 10-5.1 center dot PO20.5 center dot t-0.5 where P-O2 corresponds to the partial pressure of O-2 (in bar) and t is time in seconds. Different mechanisms are proposed to explain the evolution with time of the O-2 consumption during pyrite oxidation: (i) decrease of the specific or reactive surface area after oxidation of fine grains of pyrite, (ii) decrease of O-2 pressure, (iii) growing up of secondary minerals (Fe-oxides or anhydrite in ...